The Influence of Marketing Mix, Perceived Risk, and Satisfaction on Word of Mouth in XYZ Clinic - Murpraptomo, Saka Haditya; Yuliati, Lilik Noor; Sartono, Bagus (Journal of Consumer Sciences, 2019)
The increasing need for health services, peoples who lived in the Pekayon, Bekasi City were given the opportunity to choose the right clinic. Word of mouth is a marketing technique that can be used by clinics. This study aims to analyze the effects of the marketing mix, perceived risk, and satisfaction on word of mouth at XYZ clinic. The research is a descriptive method with a survey using questionnaires and 200 respondents as the sample. Furthermore, the data analysis technique is descriptive with SPSS16.0 software and Structural Equation Model (SEM) with LISREL 8.70. Based on the results, it can be concluded that the marketing mix has a positive effect on perceived risk, marketing mix has a positive effect on satisfaction, perceived risk has a negative effect on satisfaction, marketing mix has a positive effect on word of mouth, perceived risk has a negative effect on word of mouth, and satisfaction has a positive effect on word of mouth. Referring to these conclusions, it can be confirmed that the clinical management of doctor XYZ needs to improve employee services, convenience the patient that this clinic has expert doctors, and utilizing the use of social media as a marketing strategy.